2015
DOI: 10.1136/bmjopen-2015-008204
|View full text |Cite
|
Sign up to set email alerts
|

Identification of reciprocal causality between non-alcoholic fatty liver disease and metabolic syndrome by a simplified Bayesian network in a Chinese population

Abstract: ObjectivesIt remains unclear whether non-alcoholic fatty liver disease (NAFLD) is a cause or a consequence of metabolic syndrome (MetS). We proposed a simplified Bayesian network (BN) and attempted to confirm their reciprocal causality.SettingBidirectional longitudinal cohorts (subcohorts A and B) were designed and followed up from 2005 to 2011 based on a large-scale health check-up in a Chinese population.ParticipantsSubcohort A (from NAFLD to MetS, n=8426) included the participants with or without NAFLD at b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
69
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 66 publications
(35 reference statements)
5
69
0
4
Order By: Relevance
“…Growing evidence suggested that there was bidirectional association between NAFLD with MetS and T2DM [1416]. A series of prospective studies showed that NAFLD strongly increased MetS and T2DM incident risk [7,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Growing evidence suggested that there was bidirectional association between NAFLD with MetS and T2DM [1416]. A series of prospective studies showed that NAFLD strongly increased MetS and T2DM incident risk [7,33].…”
Section: Discussionmentioning
confidence: 99%
“…Although growing evidence suggested that the NAFLD-T2DM relation is bidirectional [1315], few studies simultaneously investigated the bidirectional association between NAFLD and T2DM in a prospective setting [16]. Therefore, in the present study, we aimed to address the bidirectional relationship between NAFLD and T2DM in a prospective cohort study among a middle-aged and elderly Chinese population.…”
Section: Introductionmentioning
confidence: 99%
“…6,19 A recent study from the China Stroke Primary Prevention Trial also found that baseline proteinuria as measured by dipstick was an independent risk factor for first incident stroke and ischemic stroke. 20 A meta-analysis of cohort studies or randomized controlled trials also concluded that increasing albuminuria increased the risk of stroke. 21 Findings from the current study extend those from previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not have the data of liver biopsy as the gold standard for diagnosis in this cohort. Fourthly, the inherent limitation of non‐invasive indices by using parameters belonging to the domain of MetS is that they might fail to take into account the dynamic and bidirectional relationship linking NAFLD with MetS . Some individuals who have fatty liver now may develop MetS feature later .…”
Section: Discussionmentioning
confidence: 99%
“…Fourthly, the inherent limitation of non-invasive indices by using parameters belonging to the domain of MetS is that they might fail to take into account the dynamic and bidirectional relationship linking NAFLD with MetS. [59][60][61][62] Some individuals who have fatty liver now may develop MetS feature later. 30 On the contrary, as amount of steatosis decrease with advance fibrosis, some patients with NAFLD may be misdiagnosed.…”
Section: Discussionmentioning
confidence: 99%